Exploring the impact of covid-19 movement control order (MCO) on microenterprises in Rantau Panjang, Kelantan, Malaysia / Nik Zam Nik Wan ...[et al.] - Nik Wan, Nik Zam; Razak, Syuhaila; San, Suzana; Saidi, Noraida; Abdullah@Abd Aziz, Azilawati (Universiti Teknologi MARA Cawangan Pahang, 2021)
Corona Virus (COVID-19) is a pandemic outbreak that severely claimed millions of lives worldwide. Among the actions taken by the Malaysian Government to prevent further spread of COVID-19 was to impose travel restrictions and Movement Control Order (MCO). Most activities including economic activities were weakening along the duration of MCO. Businesses in Rantau Panjang, Kelantan are among the microenterprises that were massively affected. Rantau Panjang which is known as one of the popular attractions in Kelantan is highly affected when MCO and CMCO were imposed because it had disapproved inter-state and inter-district travel. Since the businesses require face-to-face trading activities, MCO would definitely affect the businesses enormously. This study embarked after almost a year of the pandemic outbreak with an objective to explore the extent to which COVID-19 MCO inclusive of RMCO and CMCO has affected microenterprises in Rantau Panjang, Kelantan. This study applies qualitative approach utilizing structured face-to-face interviews. It was identified that more than 80% of the participants experienced reduction in sales with 67% stated that they experienced sales dropped of more than 50% while 7.4% notify that they suffered 100% sales dropped indicating that they had no sales at all through the MCO, CMCO and RMCO period. This study is considered to be important because the resilient of these microenterprises would reflect the sustainability of these places as Kelantan's tourist attraction that boosts economic activities